A comparison of four antiepileptic drugs in status epilepticus: experience from India. (1st November 2016) - Misra, Usha Kant; Kalita, Jayantee
Abstract : Purpose : We report the efficacy and safety of lorazepam (LOR), phenytoin (PHT), valproate (VPA) and levetiracetam (LEV) as first and second choice antiepileptic drug (AED) in status epilepticus (SE) and their combinations in preventing refractory SE. Materials and methods : The results of our two earlier trials on SE were compared; one evaluated VPA versus PHT (group I) and the other LOR versus LEV (group II). In group I, additional patients were recruited in addition to published data. The primary outcome was cessation of SE after first and second AEDs and secondary outcome was mortality and side effects. The efficacy of these four drugs as first and second choice was compared. The frequency of refractory seizure in groups I and II and their contributing factors were analyzed. Results : One hundred and seventeen patients were in group I and 79 in group II. The baseline characteristics of the patients were similar in LOR, LEV, VPA and PHT groups. As a first choice, LOR controlled SE in 75.1%, LEV in 76.3%, VPA in 55.4% and PHT in 44.2% patients. As a second choice, LEV was effective in 88.9%, LOR in 70%, VPA in 74.1% and PHT in 25% patients. Refractory SE was more frequent in group I than group II (29.9% versus 10.5%), however, complications and mortality were higher in group II. Conclusion : LOR and LEV combination was superior in reducing refractory SE but at the cost of higher complications and death.